Price Formation on Stock Exchanges: The Evolution of Trading within the Day - Gerety, Mason S.; Mulherin, J. Harold (Review of Financial Studies, 1994)
Prior analyses of prices of the NYSE and other exchanges find that transitory price volatility is greater at the open of trading than at the close. We extend this line of research by using 40 years of hourly Dow Jones 65 composite price index data to estimate transitory volatility throughout the trading day. Our results indicate that transitory volatility steadily declines during the trading day. We find a similar intraday decline in transitory volatility for a 2½-year sample of the individual firms in the Dow Jones 30 Industrials Index. The results are consistent with the hypothesis that trading aids price formation and do not support the argument that particular trading mechanisms are the source of greater volatility at the open of trading.